COVID-19 Infection in Renal Transplant Recipients: Experience from a Tertiary Care Center in Nepal - Bhurtyal, Nishan; Shah, Dibya S (Journal of Institute of Medicine Nepal, 2022)
Introduction COVID-19 pandemic has challenged the health system globally specially the low to middle income countries. Renal transplant recipient is at risk due to immunosuppressed state. The course of the disease and its outcome is not completely known and there is scarcity of information from developing world. Methods The study was carried out at Tribhuvan University Teaching Hospital, Kathmandu from May 2020 till May 2021. All of the renal transplant recipients infected with COVID-19 virus were included in the study. Duration of transplantation, recipient’s comorbidities, clinical presentation including laboratory investigations and outcome in terms of hospitalization, need of intensive care, and need of mechanical ventilation, organ failure and mortality were studied. Results There were 71 patients (male/female: 60/11, mean age 42.6+10.4) were included in the study. 72% patients (n=51) required hospitalization. There were 15 patients (21%) who expired. Patients requiring mechanical ventilation were 14(19.7%), 24(33.8%) required intensive care, 10 (14%) required hemodialysis support during admission. A prior history of rejection, presence of diabetes, graft dysfunction at baseline, and a higher creatinine at baseline was associated with mortality. Hypoxia, leucopenia, lymphopenia was predictive with mortality. Raised inflammatory markers as d-Dimer, LDH, development of acute kidney injury was associated with mortality. Presence of Acute kidney injury was associated with increased risk of mortality, need of intensive care and prolonged hospitalizations. Conclusion COVID-19 infection in renal transplant recipients carries a high risk for mortality. The factors that correlated with risk for mortality were hypoxia, leucopenia, high inflammatory markers and need of mechanical ventilation.